Experimental and Numerical Analysis of a Sphere Falling into a Viscous Fluid - Cruchaga-Ssa., M (2012)
The experimental and numerical analysis of spheres falling into viscous flows is considered. The physical model is built using a set of silicone and glass spheres falling into oil and water. The rigid-body trajectory of the sphere and the free surface evolution are obtained from videos. The numerical results are obtained using two different finite element codes. The first code uses a fractional step approach with adaptive meshes and time-step sizes whereas the second code uses a monolithic fully coupled fixed-mesh technique. The results exhibit a good comparison between both numerical techniques and with the experiments. © 2011 John Wiley & Sons, Ltd.